Surplus diagram and cascade analysis technique for targeting property-based material reuse network - Chwan, Dominic Yee Foo; Kazantzi, Vasiliki; El-Halwagib, Mahmoud M.; Abdul Manan, Zainuddin (Elsevier BV, 2006)
Recycle of process and waste streams are among the most effective resource conservation and waste reduction strategies. In many cases, recycle/reuse is dictated by sink constraints on properties of the recycled streams. In this work, we introduce an algebraic technique to establish rigorous targets on the minimum usage of fresh resources, maximum direct reuse, and minimum waste discharge for property-based material reuse network. Two new tools have been developed. A new graphical tool called the property surplus diagram is firstly introduced to provide a basic framework for determining rigorous targets for minimum fresh usage, maximum recycle, and minimum waste discharge. The tools also determine the property-based material recycle pinch location. The Property Cascade Analysis (PCA) technique is next established to set targets via a tabular approach. PCA eliminates the iterative steps typically associated with a graphical approach. Along with the minimum fresh and waste targets, the material allocation target is another key feature of the PCA. A network design technique is also presented in this paper to synthesise a maximum resource recovery (MRR) network that achieves the various established targets. The procedures developed in this paper constitute a generalisation to the composition-based graphical and algebraic techniques developed for water and hydrogen recovery networks. Two case studies are solved to illustrate the applicability of the developed procedures.